Transmedia Storytelling and Civic Culture: "Peace is my Inclusive Tale": Project for Children with Visual or Hearing Impairments - Cardozo Rivera, Ismael; Madariaga Ortuzar, Aurora (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article describes the process of an action research whose objective was the productions of a transmedia storytelling called "La Paz es mi Cuento Inclusiva" (https://www.lapazmicuentoinclusiva.com/), based on the application of a methodological guideline. aimed at children with visual or hearing impairments. It begins with a theoretical framework around transmedia narratives and their adaptation to an inclusive context. Subsequently, the scope of the application of the methodological guideline in children of three institutions in Cali, (Colombia) is presented; and Finally, the Inclusive Transmedia Storytelling is presented as a validator of the work carried out, and its impact around social inclusion from functional diversity and civic culture.